Pengaruh Financing To Deposit Ratio Dan Non Performing Financing Terhadap Return On Asset: Studi Kasus pada Enam Bank Umum Syariah di Indonesia Periode 2014-2018 - Sastra, Heri; Ariziq, Bhandan; Sukartaatmadja, Iswandi (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
This research is to prove the influence on Financing To Deposit Ratioa (FDR) and Non Performing Financing (NPF) on Return On Asset (ROA). The analysis technicque used is regression analysis, because the data used are secondary data to determine the accuracy of the regression model. The dependent variable of thus research data is Return On Asset (ROA), the independent variebles are Financing To Deposit Ratio (FDR) and Non Performing Financing (NPF). The result of this study indicate that if Financing To Deposit Ratio (FDR) have a negative and significant effect on Return On Asset (ROA), these results are evidenced by a t-test of t velue of -2.228 and the significance velue indicates a figure of 0.034. Non Performing Financing (NPF) have a negative and signifivant effect on Return On Asset (ROA), these results are evidenced by a t-test og t velue of -6.269 and the significance value indicate a figure of 0.000. Keywords : Financing To Deposit Ratio (FDR), Non Performing Financing (NPF), Return On Asset (ROA).